Interactions between societal goals and restoration of dry forest landscapes in western North America - Franklin, Jerry F; Hagmann, R. Keala; Urgenson, Lauren S (Landscape ecology, 2014)
Millions of acres of dry, frequent-fire woodlands and forests in western North America are the focus of multi-million dollar ecosystem restoration and fuel treatment activities. Societal awareness and engagement with these ecosystems has intensified due to recent mega fires and projections for increased vulnerability of these systems to fire, insects, and drought-related stressors. Also, the importance of goods and services provided by dry forests has expanded to include many values, such as watershed protection, habitat for biodiversity, and recreation as well as timber. Public awareness of fire and other risks associated with current conditions in dry forests generally is high and broad support exists for active management over passive alternatives. Efforts to integrate scientific principles with societal goals in dry forest restoration programs are encouraging but significant social barriers remain related to funding, conflicting goals (e.g., smoke vs. human health and restoration vs. preservation of species habitat), and stakeholder trust. The limited area restored relative to the extensive vulnerable area suggests that the seriousness and complexity of the threats are not fully appreciated or not given sufficient priority for funding, despite stated preferences for restorative management. Hence, challenges remain. Societal choices ultimately determine the goals, extent, and methodology of dry forest restoration programs with science stimulating and informing policy and management decisions.